The association between vital signs at hospital admission and adverse outcomes in patients with COVID-19: a retrospective cohort study - Murzabekov, Marat; Lidströmer, Niklas; Borg, Niklas; Runold, Michael; Herlenius, Eric; Rautiainen, Susanne (Frontiers in Medicine, 2025)
BackgroundVital sign measurements at hospital admission are used to identify patients at risk for adverse events. However, how vital signs at admission are related to adverse outcomes among COVID-19 patients is not fully characterized.ObjectivesTo characterize vital signs at admission and their associations with intensive care unit/intermediate care unit (ICU/IMCU) admission and in-hospital mortality in adult patients with COVID-19.MethodsThis retrospective cohort study included 2,826 adults admitted with COVID-19 to Karolinska University Hospitals, Stockholm, Sweden, between 2 March 2020 and 1 June 2021. The Cox proportional hazards model was used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) for associations between vital signs at admission and ICU/IMCU admission and in-hospital mortality.ResultsThe median age was 62.2 years, and 62.1% were men. Each unit increase in respiratory rate (HR 1.03, 95% CI 1.02–1.05), heart rate (HR 1.01, 95% CI 1.00–1.02), temperature (HR 1.21, 95% CI 1.11–1.32), and each unit decrease in saturation (HR 1.05, 95% CI 1.04–1.06) were associated with ICU/IMCU admission. Respiratory rate (HR 1.04, 95% CI 1.02–1.07) and saturation (HR 1.04, 95% CI 1.02–1.06) were also associated with in-hospital mortality. These associations persisted across pandemic waves.ConclusionRespiratory rate and lower saturation at admission were associated with increased ICU/IMCU admission and in-hospital mortality. Our findings suggest that greater emphasis on respiratory rate and oxygen saturation in early warning scores—such as the revised Sequential Organ Failure Assessment (SOFA) score and other sepsis prediction models, to improve risk stratification of viral sepsis, especially in patients with COVID-19.